A bi-directional, direct conversion converter for use in household renewable energy systems - Schutte, Adriaan Nicholaas (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScIng (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.